2020
DOI: 10.1097/crd.0000000000000324
|View full text |Cite
|
Sign up to set email alerts
|

Loeffler’s Endocarditis and Hypereosinophilic Syndrome

Abstract: Loeffler's endocarditis and hypereosinophilic syndromes are a unique group of infiltrative disorders characterized by hypereosinophilia, inflammatory thrombotic, and ultimately, fibrotic involvement of the heart leading to multiple complications including valve involvement, thromboembolic phenomena, heart failure. Clinical recognition, comprehensive laboratory and multimodality imaging diagnostic workup, and early initiation of treatment have been shown to slow down the progression and promote remission. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 78 publications
(221 reference statements)
0
25
1
Order By: Relevance
“…Loeffler's endomyocarditis is considered when there is isolated myocardial involvement. Congestive heart failure and extensive myocardial involvement are seen in the majority of the patients [22]. In the current study, eosinophilic infiltration was not observed in the histopathological evaluation of other organs.…”
Section: Discussioncontrasting
confidence: 52%
“…Loeffler's endomyocarditis is considered when there is isolated myocardial involvement. Congestive heart failure and extensive myocardial involvement are seen in the majority of the patients [22]. In the current study, eosinophilic infiltration was not observed in the histopathological evaluation of other organs.…”
Section: Discussioncontrasting
confidence: 52%
“…Endomyocardial biopsy is the gold standard for diagnosing Loeffler endocarditis ( 14 ); however, no clinical guidelines for managing Loeffler endocarditis are currently in vogue, and treatment expertise is mostly derived from a handful of previous case reports. The management of Loeffler endocarditis requires consideration of the etiology of eosinophilia, the stage of progress, and the involvement of organs ( 3 ). The treatment goals should include the following: (1) eosinophils being reduced to the normal range to avoid cardiac damage (eosinophils can release toxic substances), and (2) treatment of the underlying etiology and complications (heart failure, arrhythmia, thrombus).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, early identification and effective treatment are crucial for improving the prognosis. However, no consensus guidelines are available for managing Loeffler endocarditis ( 3 ), because the management treatment of each patient is individualized and relates to (1) an acute treatment, (2) a symptomatic cardiac treatment based on diverse manifestations (anti-arrhythmics, pressure support, ejection fraction support (EF support), thrombus targeting, prophylaxis, etc. ), and (3) finally a thorough diagnostic workup to identify the cause of eosinophilia (idiopathic, primary, or secondary).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have reported that approximately 60% of patients with IHES suffer from heart damage ( Ogbogu et al, 2007 ; He et al, 2020 ). Cardiac involvement secondary to IHES was reported to be the leading cause of death ( Ogbogu et al, 2007 ; He et al, 2020 ; Salih et al, 2021 ). Cardiac injury caused by HES occurs in three stages ( He et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%